Demonstration of pulmonary arteries by contrast injection into pulmonary vein. Issue 1 (January 1978) - Singh, S P; Rigby, M L; Astley, R
Abstract : Pulmonary venous injection of contrast medium in the near-wedge position produced a flow into the pulmonary arterial tree in 15 out of 21 children with cyanotic congenital heart disease. In 5 there was good opacification of both sides from a single injection. The technique provides an additional method of demonstrating the anatomy of the pulmonary arteries where surgical treatment is contemplated.